Design Commercial Complex, Considering Environment - Sahebpoor, Vesal; Abhari, Sepehr Asgarian (Advances in Social Sciences Research Journal, 2024)
This study examines to design the commercial, official, and entertainment complex according to regional typological approach. The aim of this study is to create a pleasant environment for buying goods, receiving official service, entertainment and communication of human. In order to access the goal, the researchers’ focused on the history of commercial and official in Iran. Moreover, the researchers investigate the evolution of the complexes during the history. The main objective of this study is to design the complex properly according to the regional typological approach. The researchers analyzed the site through different directions as follows a) the placement of building on the site b) the directions of building and entrances. The researchers tried to have the building that has the best harmony with the environment. The researchers received the most important tools from the site analysis. Physical planning determined required spaces and their measurements. It is obvious that the researchers considered the concept, view according to the site features in order to access the best concept and design.